Penyuluhan Kesehatan Mengenai Program 3cp (Cara Penyimpanan Obat, Cara Penggunaan Obat, Cara Pemusnahan Obat) dan Penanganan Terhadap Penyakit DBD - Cindy Zahira Putri; Lira Syara Sabila; Shela Ayu Safitri; Ameldyah Pramesti; Alya Naura Tifania Ayu; Putri Regina; Nabila Adelia Ramadhani; Tri Trisnamiati; Baharudin Darusman; Renata; Rizka Novia Atmadani (PASAI : Jurnal Pengabdian kepada Masyarakat, 2025)
Health is a basic need that is important to maintain. Preventive efforts through education are needed to increase public awareness, including in drug management and prevention of infectious diseases. This community service activity aims to provide education on 3CP (Methods of Storing, Using, and Destroying Drugs) and preventing Dengue Hemorrhagic Fever (DHF) to residents of the Rahadi Oesman Dormitory, Malang. The counseling was held on May 25, 2025 and was attended by 14 participants. The methods used were lectures, discussions, and question and answer sessions. The material includes proper drug storage, use according to the rules, and how to safely destroy expired drugs. Education also includes knowledge about DHF, including symptoms, stages of the disease, and preventive measures such as 3M (draining, covering, and burying), as well as maintaining environmental cleanliness. The pretest results showed that 50% of participants did not understand the material well. However, after the counseling, there was an increase in the score on the posttest, which indicated an increase in understanding. This activity not only increased participants' knowledge, but also formed awareness of the importance of clean and healthy living behavior and proper drug management. Thus, this counseling is expected to be the initial step in preventing drug abuse and the spread of DHF in residential environments.